Influence of Bran Particle Size on Bread‐Baking Quality of Whole Grain Wheat Flour and Starch Retrogradation. Issue 1 (13th January 2014) - Cai, Liming; Choi, Induck; Hyun, Jong‐Nae; Jeong, Young‐Keun; Baik, Byung‐Kee
ABSTRACT: The influence of bran particle size on bread‐baking quality of whole grain wheat flour (WWF) and starch retrogradation was studied. Higher water absorption of dough prepared from WWF with added gluten to attain 18% protein was observed for WWFs of fine bran than those of coarse bran, whereas no significant difference in dough mixing time was detected for WWFs of varying bran particle size. The effects of bran particle size on loaf volume of WWF bread and crumb firmness during storage were more evident in hard white wheat than in hard red wheat. A greater degree of starch retrogradation in bread crumb stored for seven days at 4°C was observed in WWFs of fine bran than those of coarse bran. The gels prepared from starch–fine bran blends were harder than those prepared from starch–unground bran blends when stored for one and seven days at 4°C. Furthermore, a greater degree of starch retrogradation was observed in gelatinized starch containing fine bran than that containing unground bran after storage for seven days at 4°C. It is probable that finely ground bran takes away more water from gelatinized starch than coarsely ground bran, increasing the extent of starch retrogradation in bread and gels during storage.